Grooming behaviour in the Red-tailed guenon - Jonsved, David (SLU/Dept. of Animal Environment and Health (until 231231), 2015)
The behaviour of the red-tailed guenon (Cercopithecus ascanius) was studied over the course of nine days in the Sabaringo forest surrounding Kichwa Tembo Tented Camp near the Masai Mara National Reserve, Kenya. A focal animal instantaneous sampling method with a one minute interval was used to record the behaviours of the monkeys for approximately 12 hours a day, the day being divided into six shifts á two hours. This method has proven successful in earlier studies of red-tails in this area. The study subjects included both lactating and non-lactating females, juveniles and on some occasions the resident male. The purpose of this study was to examine the grooming behaviour of red-tailed guenons and whether or not the occurrence of grooming varies depending on monkey type (lactating or non-lactating) and time of day. The results show that grooming occurs throughout the day with the morning (09:00) being the period when most grooming occurs. It was also found that lactating females spent slightly more of their time grooming than did non-lactating individuals. Presented at the end of the discussion are suggestions for further research in this area, including the possible role of facial expressions and other subtle social signals, the significance of which body parts are being groomed as well as the different functions of grooming.